2017
DOI: 10.1093/nar/gkx109
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human telomere RNA G-quadruplex structures in vitro and in living cells using 19F NMR spectroscopy

Abstract: Human telomeric RNA has been identified as a key component of the telomere machinery. Recently, the growing evidence suggests that the telomeric RNA forms G-quadruplex structures to play an important role in telomere protection and regulation. In the present studies, we developed a 19F NMR spectroscopy method to investigate the telomeric RNA G-quadruplex structures in vitro and in living cells. We demonstrated that the simplicity and sensitivity of 19F NMR approach can be used to directly observe the dimeric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
131
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 58 publications
(49 reference statements)
0
131
0
Order By: Relevance
“…[17] In addition, as expected, we found that some of the QUMA-1 foci gradually disappeared during the observation period, while new fluorescent foci appeared ( Figure 5C and the Supporting Information, Figure S38). [18] Taken together, these continuous,real-time results revealed the complexity of the dynamics of RNAG -quadruplexes in live cells.T he molecular probe QUMA-1 potentially provides ap romising tool for exploring the nature,m echanism, and significance underlying such interesting dynamics. [18] Taken together, these continuous,real-time results revealed the complexity of the dynamics of RNAG -quadruplexes in live cells.T he molecular probe QUMA-1 potentially provides ap romising tool for exploring the nature,m echanism, and significance underlying such interesting dynamics.…”
mentioning
confidence: 82%
“…[17] In addition, as expected, we found that some of the QUMA-1 foci gradually disappeared during the observation period, while new fluorescent foci appeared ( Figure 5C and the Supporting Information, Figure S38). [18] Taken together, these continuous,real-time results revealed the complexity of the dynamics of RNAG -quadruplexes in live cells.T he molecular probe QUMA-1 potentially provides ap romising tool for exploring the nature,m echanism, and significance underlying such interesting dynamics. [18] Taken together, these continuous,real-time results revealed the complexity of the dynamics of RNAG -quadruplexes in live cells.T he molecular probe QUMA-1 potentially provides ap romising tool for exploring the nature,m echanism, and significance underlying such interesting dynamics.…”
mentioning
confidence: 82%
“…Despite extensive studies, probing different GQ topologies and their ligand‐binding abilities in a cellular environment has remained a major challenge 25, 26, 27. For example, structural analysis of GQs in the cell requires elaborate assay setups and expensive isotope‐labeled ONs in non‐apoptotic concentrations, which often leads to obscure signals due to the inhomogeneity of cellular samples 25.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly,t hese chemically tagged ASOs have significantly poorer downregulation properties than the regular untagged ASO, as shown by quantitative reverse transcription polymerase chain reaction( qRT-PCR) for pharmaceutically relevant doses of 1.25 mm [(67.9 AE 5.1) %f or unmodified ASO, (34.9 AE 8.9) %f or biotin-labelled and (37 AE 17) %f or Cy3-labelledA SO, Figure 2E;d etails in Sections 1.9, 1.10, 2.1-2.3, 2.6, 2.7 in the Supporting Information]. Because the tagged versions are significantly less efficient, they might not reflect how untagged ASO behaves in the cell, thus highlighting the problem that drug modifications with, for example, fluorescent or biotin tags can alter activity or localization and emphasizingt he need for at ag-free technique.In-cell NMR spectroscopy is at ag-free technique and allows the study,a ta tomic resolution,o fs tructural properties of, for example, proteins [7][8][9][10][11][12][13] and small DNA/RNA hairpins [14][15][16][17] in cells. Therefore, the ASO was delivered into HEK293T cells by electroporation,a su sed previously fors olution-state in-cell NMR studies, [9,17] to ensure robust uptake, and ac lassical in-cell solution-state NMR spectrum was acquired.…”
mentioning
confidence: 99%
“…In addition to the 1D CP spectrum,a 2D 1 H, 31 PC P-PASS [29] in-cell spectrum could be acquired within 2h 40 min to verify the isotropic chemical shift of the bound ASO ( Figure 3C). Although solution-state in-cell NMR investigation of transfected oligonucleotides has been carried out before, [14][15][16][17] the ASO investigated hered id not produce any signal detectable by this technique.T his suggestst hat the amount of free intracellular ASO is low and that the ASO insteade xists in the form of macromolecular complexes with mRNA and/ord ifferent proteins, as might be expectedf rom the literature. [2,4,18] To overcome the current limitations of solution-state in-cell NMR (sensitivity,s tabilitya nd size) we presentafrozen in-cell DNP approach.T ot he best of our knowledge,t his is the first time that DNP has been used to detect an exogenous oligonucleotide delivered into cells, and also the first time that at ransfected antisense drug in macromolecular complexes has been detected in intact human cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation